Impact of Organizational Agility on Institutional Excellence in Municipalities of Jordan - Harahsheh, Faraj (Journal of Cultural Analysis and Social Change, 2025)
This study aimed to explore the impact of organizational agility on institutional excellence in municipalities of Jordan (case study on the municipalities of Jerash Governorate). This study examined the impact of organizational agility on institutional excellence in municipalities in Jordan from the perspective of service recipients (public sector, private sector, local community). The primary objective of this study was to identify the impact of organizational agility dimensions "flexibility, responsiveness, innovation, sensing agility on institutional excellence in Jordanian municipalities. The researcher used a descriptive and analytical research method to achieve the study's objectives. A questionnaire was used to conduct this study and a convenient random sample of "200" service recipients was selected. The researcher used several statistical methods, the most important of which were arithmetic averages, ANOVA testing, and the "SPSS" statistical package. The results of the study showed that service recipients' perceptions of organizational agility in the dimensions of "flexibility and responsiveness" were moderate, while the study sample's perceptions of organizational agility in the dimensions of "innovation and sensing agility" were high. The study also demonstrated a positive impact of organizational agility on institutional excellence in Jordanian municipalities. The study recommended paying great attention to the flexibility of service provision and responsiveness to service recipients through training and raising the efficiency of employees in the municipal sector and providing material and technical capabilities, as well as enhancing employee innovation and responsiveness. The study presented recommendations for conducting a study on the impact of organizational agility on institutional excellence from the perspective of municipal employees. The study provided important practical contributions related to the dimensions of organizational agility and its impact on institutional excellence, which can be used by municipal officials to improve institutional excellence. It also provided contributions related in providing a conceptual framework for organizational agility and institutional performance.